Perspectives on the use of the Fraction Strips application in teaching fractions - Huarsaya-Jove, Nicol Gabriela; Vilca-Valdez, Micaela Yeri; Turpo-Gebera, Osbaldo (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2023)
The COVID-19 pandemic has exposed the digital divide and the limited tech- nopedagogical proficiency of teachers. To improve the teaching of fractions, thirty elementary school teachers were trained in the use of the Fraction Strips virtual manipulative. Phenomenology was used to assess their learning experiences and the dynamics of technological appropriation were recorded. The results showed a significant appropriation of the manipulative, the importance of multiple rep- resentations in the conceptual understanding of fractions and the promotion of meaningful and discovery learning. In conclusion, the training improved the teach- ers' digital competencies and pedagogical practices.